The Social Lives of Gender and Religion: Implications for Development Policy. (May 2016) - Mee, Wendy
Abstract: To date, the literature on 'gender and development' has remained largely sequestered from that on 'religion and development', and consequently the presence of conceptual problems common to the two fields has gone largely unremarked. This paper identifies three such conceptual problems, here termed categorization, identification and representation. The oversight of common conceptual problems has important implications for the assessment of religion and gender in sustainable development policy. One such effect, I argue, is the consolidation of a narrow range of negative and secularist readings of the potential role of gender and religion in sustainable development. To circumvent conceptualizations that may give rise to prejudicial readings of gender and religion, this paper follows feminist and religious studies scholars in arguing that we conceive of gender and religion as permeable categories and non‐exclusive identities, constituted by diverse discursive elements. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment.